Don't Stop Believin' – Heterogeneous Updating of Intergenerational Mobility Perceptions across Income Groups - Anna Schwarz; Philipp Warum (Center for Economic Studies and ifo Institute (CESifo), 2023)
This article presents a novel explanation why demand for redistribution on average does not respond to information on low intergenerational mobility. Building on insights from behavioral economics, we expect that incentives to update perceptions of intergenerational mobility change along the income distribution. Empirically, we conduct a survey experiment in Austria and show that the average treatment effect of information on perceptions is mostly driven by higher income individuals while low-income respondents hardly react. We replicate this result for the United States and Germany using data from two closely related survey experiments (Alesina, Stantcheva, and Teso, 2018; Fehr, Müller, and Preus, 2022). Thus, the frequently observed unresponsiveness of demand for redistribution may result because the group which drives the effect on beliefs does not increase demand for redistribution and may even decrease it. Indeed, despite the strong perception shift in the high-income group, the treatment effects on its preferences are mostly zero and even negative for certain policies. At the same time, the group with the clearest incentives to change its redistributive preferences, the low-income group, is systematically less inclined to update its perceptions and thus their redistributive preferences are mostly unaffected and only partially increased in response to the treatment. We suggest that different responses to information could be due to motivated beliefs, since high social mobility implies for low-income earners that effort is more likely to pay off.
Keywords: C93; D63; D83; H23; J62; 330; intergenerational mobility; beliefs; survey experiment; redistributive preferences